Using CIPP Model to Evaluate the Effectiveness of Flexible Learning Implementation in Satya Wacana Christian University - Dwikurnaningsih, Yari; Waruwu, Marinu; Wasitohadi, Wasitohadi (Jurnal Pendidikan Progresif, 2023)
Using CIPP Model to evaluate the effectiveness of flexible learning implementation in Satya Wacana Christian University. Purpose: This study aims to assess the effectiveness of flexible learning-based learning at the university level. Method: The research approach uses a mixed method with a sequential explanatory model. The quantitative method is used in the first stage then the qualitative method is used in the second stage. The research subjects were 19 lecturers and 150 students and 1 head of the Bureau of Technology and Information Systems (BTSI) who manages f-learn. The qualitative of the data was obtained through interviews and document study analyzed using Miles and Huberman's model. Quantitative data obtained from numbers with descriptive analysis. Findings: The results showed that the evaluation of context aspects of learning-based f-learn was in the very good category, the evaluation of input aspects was in the good category, the evaluation of process aspects was in the good category, and the evaluation of product aspects was in the good category. Conclusion: Thus, f-learn-based learning has an impact on increasing students' and lecturers' knowledge and mastery of information technology. The drawback is that it needs improvement for the quality of the internet network for each student, which is different. Keywords: cipp model, effectiveness, evaluation, learning, online.DOI: http://dx.doi.org/10.23960/jpp.v13.i2.202310